CABOCLINHO AND THE TEACHING OF INDIGENOUS HERITAGE THROUGH DANCE - Cabral de Arruda Junior, Otacílio (Revista Gênero e Interdisciplinaridade, 2024)
The caboclinho is an artistic performance that combines elements of dance to narrate the stories of warriors and heroes, strongly influenced by indigenous culture. This performance embodies the historical ancestry of the Brazilian nation and serves as an expression of popular culture with a century-old tradition, with dance as its identifying element. The general objective of this article is to reflect about caboclinho dance as a useful element for teaching indigenous culture, conducted through bibliographic research. The findings indicate that caboclinho, through the body and within the context of art education in dance, contains elements, signs, and symbols useful for strengthening the teaching of indigenous heritage and Brazilian cultural identity, thereby demystifying foreign influences in Brazil. Consequently, caboclinho dance can be incorporated into the arts curriculum, presenting concepts, definitions, and necessary tools for decisions related to the conservation of indigenous heritage. It also encourages those interested in studying popular culture, meeting the requirements set by Law 11.645/2008.